Double-MOFs (Metal-Organic Frameworks) derived composite carbon-based loaded Co-MnO2 catalyst as well as preparation method and application thereof
By constructing miniaturized ZIF-67 nanoparticles on the surface of Ce-BTC nanorods and doping them with manganese metal, a double MOFs core-shell composite material was formed, and a double MOFs derived composite carbon-based supported Co-MnO2 catalyst was obtained through inert atmosphere calcination. The high cost of precious metal catalysts and limited performance of single metal catalysts have achieved efficient and stable catalytic reduction reactions and have good magnetic separation performance.
Patent Information
- Application Number
- CN202411597711.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-18
AI Technical Summary
The prior art uses precious metal catalysts to catalyze the reduction of nitrobenzene compounds to amine compounds, which are limited by high cost and scarcity, and the catalytic performance of single metal catalysts is limited, making it difficult to meet the needs of industrial applications.
By using Ce-BTC one-dimensional nanostructure as a carrier, miniaturized ZIF-67 nanoparticles on the surface and doped with manganese metal to form a CoMn bimetal site, a double MOFs core-shell composite material was obtained, and then calcined in an inert atmosphere to form a slight with A two-MOFs-derived composite carbon-based supported Co-MnO2 catalyst with one-dimensional hollow nanostructures.
This catalyst exhibits superior catalytic performance and stability in catalytic reduction of nitrobenzene pollutant reaction, has good magnetic separation performance, and significantly improves the catalytic activity and stability of Co nanoparticles.
Smart Images

Figure CN119456010A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nanocatalyst preparation, and in particular to a dual MOFs-derived composite carbon-based loaded Co-MnO2 catalyst, a preparation method and an application thereof. Background Art
[0002] Currently, the catalytic reduction of nitrobenzene compounds to amine compounds using active metal solid catalysts is considered to be an effective method for treating and utilizing these highly toxic and carcinogenic nitrobenzene pollutants. This method can efficiently and sustainably convert these highly hazardous pollutants into commercially valuable, low-toxic substances, and plays an important role in the conversion and utilization of chemical resources. Precious metal materials are well known for their catalytic performance in the efficient reduction of nitrobenzene substances, but their high cost and scarcity limit their industrial application.
[0003] In recent years, cheaper transition metals have attracted great interest from researchers as substitutes for precious metals. In particular, cobalt (Co) metal has become a commonly used non-precious metal catalyst in catalytic reduction reactions due to its unique electronic configuration and variable valence state. Since the further improvement of the catalytic performance of single metal catalysts is usually limited, the design of bimetallic catalysts can utilize the synergistic effect between two different metals to exhibit superior catalytic performance and is considered to be a better improvement solution. The regulation of morphological structure and chemical composition can significantly improve the catalytic activity of bimetallic catalysts. Therefore, the development of porous supports with different structural characteristics and effective synthesis methods of bimetallic catalytic active sites is extremely important for the preparation of more efficient and stable cobalt-based bimetallic catalysts.
[0004] Metal-organic frameworks (MOFs) are highly versatile precursors that can create porous nitrogen-doped carbon materials rich in transition metal species during pyrolysis. They can be used in the structural design of nanometal catalysts to effectively improve their catalytic performance. These MOFs-derived catalysts exhibit unique properties such as adjustable pore size, flexible preparation process, modulatable surface chemical properties and high stability. Among them, ZIF-67 is known for its highly porous topological structure and rich cobalt ions (Co 2+ ) content in the zeolitic imidazole framework. ZIF-67-derived materials provide porous nitrogen-doped carbon frameworks that can stably immobilize cobalt nanoparticles, and in situ prepare cobalt metal-supported catalysts with excellent performance by a one-step pyrolysis method. In particular, the addition of another transition metal ion (such as manganese ion Mn) during the synthesis of ZIF-67 2+), or by ion exchange, new metal active sites are introduced to form binary metal hybrid ZIF-67 (such as CoMn-ZIF-67). During the pyrolysis process, the newly introduced metal sites combine with the existing cobalt active sites to form a Co-based bimetallic catalyst, which significantly improves the catalytic efficiency and stability of the Co metal. The high polarity of Co and the second transition metal enhances the electrical conductivity and promotes the chemical adsorption and redox kinetics in the catalytic reaction. Therefore, the combination of Co-based bimetallic components in ZIF-67-derived catalysts exhibits unique bimetallic electronic effects and synergistic effects, greatly improving the catalytic reduction performance of Co-based catalysts for nitrobenzenes.
[0005] Miniaturizing MOFs to obtain small-sized nanoparticles helps to reduce the size of the derived catalyst and improve its dispersibility in the reaction medium, thereby significantly enhancing its catalytic performance. Integrating nanosized MOFs with other stable nanomaterials to form nanoscale MOFs-based composite materials with heterogeneous structures is a relatively effective construction method. In particular, Ce-BTC nanorods are low-cost, easy-to-prepare one-dimensional MOF materials. The abundant carbonyl groups distributed on their surface can serve as adsorption sites for other metal ions, which helps to immobilize these metal ions through electrostatic adsorption, and then react with specific organic ligands to achieve bridging coordination reactions with the second MOF structure to form a dual MOFs composite material. This preparation process promotes the uniform formation of smaller nanoscale MOFs entities on the surface of Ce-BTC, and Ce-BTC nanorods as carriers are in-situ converted into one-dimensional hollow tubular structures through calcination and pyrolysis, providing large specific surface area and efficient mass transfer performance, effectively supporting and dispersing the second MOF-derived catalyst, thereby enhancing the catalytic performance of this type of composite material. Summary of the invention
[0006] The present invention utilizes the advantageous characteristics of the Ce-BTC one-dimensional nanostructure, constructs miniaturized ZIF-67 nanoparticles on the surface, and at the same time, dopes the ZIF-67 structure with manganese metal to construct CoMn bimetallic sites to obtain a dual MOFs core-shell composite material (Ce-BTC@ZIF-67 / Mn); then, calcination is performed in an inert atmosphere to obtain a dual MOFs-derived composite carbon-based supported CoMn bimetallic catalyst (CeO2-C@NC / Co-MnO2) with a one-dimensional hollow nanostructure. The special structural characteristics and structure-activity relationship enable the catalyst to exhibit relatively superior catalytic performance and stability in the catalytic reduction of nitrobenzene pollutants. The preparation method proposed in the present invention provides a reliable way to synthesize miniaturized MOFs nanoparticle-supported catalytic materials and construct efficient and stable MOFs-derived bimetallic composite catalytic materials, showing good application prospects in the field of nanocatalysis.
[0007] In order to achieve the above technical objectives, the present invention mainly adopts the following technical solutions:
[0008] In a first aspect, the present invention discloses a dual MOFs-derived composite carbon-based supported Co-MnO2 catalyst, comprising:
[0009] Dual MOFs-derived composite carbon-based material and CeO2: The dual MOFs-derived composite carbon-based material and CeO2 are prepared by first in-situ growing ZIF-67 nanoparticles on the surface of Ce-BTC nanorods to obtain Ce-BTC@ZIF-67 core-shell composite materials, and then calcining in an inert atmosphere; and,
[0010] Co-MnO2 composite: The Co-MnO2 composite is the Ce-BTC@ZIF-67 core-shell composite material doped with Mn by ion exchange method. 2+ ions, and then the Co immobilized on ZIF-67 2+ and Mn 2+ The ions are formed by in situ transformation;
[0011] The Ce-BTC nanorods are obtained by heating and refluxing reaction of cerium salt and trimesic acid.
[0012] In a preferred embodiment of the present invention, in the Ce-BTC@ZIF-67 core-shell composite material, the Ce-BTC nanorods are calcined in an inert atmosphere to form CeO2-C nanotubes, the CeO2-C nanotubes contain carbon material and CeO2, wherein the carbon material is reacted to form a dual MOFs-derived composite carbon-based material, and the ZIF-67 nanoparticles and the Ce-BTC nanorods are composited and reacted to form a dual MOFs-derived composite carbon-based material.
[0013] In the catalyst, the mass percentage of CeO2 is 10-30% of the catalyst, the mass percentage of the dual MOFs derived composite carbon-based material is 30-70% of the catalyst, and the mass percentage of the Co-MnO2 complex is 10-35% of the catalyst.
[0014] In a preferred embodiment of the present invention, the Co-MnO2 composite is composed of Co nanoparticles and MnO2 nanoparticles, the mass percentage of the Co nanoparticles is 8-20% of the catalyst, and the mass percentage of the Mn component is 2-10% of the catalyst.
[0015] In a second aspect, the present invention discloses a method for preparing a dual MOFs-derived composite carbon-based supported Co-MnO2 catalyst as described in the first aspect, comprising the following steps:
[0016] (1) Ce-BTC nanorods were obtained by heating and refluxing cerium salt and trimesic acid. After Ce-BTC nanorods were activated by hydrochloric acid solution, Co was immobilized by the electrostatic adsorption effect of the carbonyl groups on their surface. 2+ ions, and then triggered a continuous bridging reaction with 2-methylimidazole ligands to in situ form ZIF-67 nanoparticles on the Ce-BTC surface to obtain Ce-BTC@ZIF-67 core-shell composites;
[0017] (2) The ZIF-67 particles in the Ce-BTC@ZIF-67 core-shell composite were subjected to Mn 2+ Ion doping, followed by calcination in an inert atmosphere, caused the Ce-BTC@ZIF-67 / Mn material to undergo a pyrolysis reaction to form a dual MOFs-derived composite carbon-based material and CeO2, while the Co immobilized on ZIF-67 2+ and Mn 2+ ions are in situ converted into a Co-MnO2 complex to obtain the dual MOFs-derived composite carbon-based supported Co-MnO2 catalyst CeO2-C@NC / Co-MnO2.
[0018] In a preferred embodiment of the present invention, in step (1), the preparation process of the Ce-BTC@ZIF-67 core-shell composite material is:
[0019] a) dispersing and dissolving cerium salt and trimesic acid in a mixed solution of deionized water and ethanol, stirring and mixing for 0.5 to 1 hour, then heating to 60 to 95° C., heating under reflux for 2 to 10 hours, cooling to room temperature, centrifuging, washing, and drying to obtain Ce-BTC nanorods;
[0020] b) Ce-BTC nanorods are dispersed in ethanol, an ethanol solution containing a cobalt salt and a hydrochloric acid solution is added, and the mixture is stirred for 0.5 to 1 h, and then a 2-methylimidazole ethanol solution is added, and the mixture is stirred and reacted at room temperature for 4 to 12 h, and the mixture is centrifuged, washed, and dried to obtain a Ce-BTC@ZIF-67 composite material.
[0021] In a preferred embodiment of the present invention, in step a), the mass ratio of the cerium salt to trimesic acid is 1:0.2-1; the volume ratio of the deionized water to ethanol is 1:0.5-1.5; and the cerium salt is any one of cerium nitrate, ammonium cerium nitrate, cerium sulfate, cerium chloride and cerium acetate.
[0022] In a preferred embodiment of the present invention, in step b), the mass ratio of the Ce-BTC nanorods, the cobalt salt, the 2-methylimidazole and the total amount of ethanol used is 1:2-10:4-20:150-360; the volume ratio of the hydrochloric acid solution to the total amount of ethanol used is 1:50-100; the molar concentration of hydrogen chloride in the hydrochloric acid solution is 0.1-0.5 mol / L; and the cobalt salt is any one of cobalt nitrate, cobalt chloride, cobalt sulfate and cobalt acetate.
[0023] In a preferred embodiment of the present invention, in step (2), the preparation process of the dual MOFs-derived composite carbon-based supported Co-MnO2 catalyst comprises the following steps:
[0024] The Ce-BTC@ZIF-67 composite material is dispersed in an ethanol solution, an ethanol solution containing manganese salt is added, the mixture is stirred and mixed at room temperature for 4 to 10 hours, centrifuged, washed, and dried to obtain a Ce-BTC@ZIF-67 / Mn composite material; the composite material is then placed in an inert atmosphere for high-temperature calcination to obtain a dual-MOFs derived composite carbon-based supported Co-MnO2 catalyst CeO2-C@NC / Co-MnO2.
[0025] In a preferred embodiment of the present invention, the mass ratio of the total amount of Ce-BTC@ZIF-67 composite material, manganese salt and ethanol used is 1:0.5~5:150~360; the inert atmosphere is selected from any one of nitrogen, argon and helium; the manganese salt is any one of manganese nitrate, manganese chloride, manganese sulfate and manganese acetate; the inert atmosphere calcination treatment conditions are: 1~5℃ / min heating rate, heating to 500~1000℃ and maintaining constant temperature for 1~5h.
[0026] In the third aspect, the present invention discloses a use of the dual MOFs-derived composite carbon-based loaded Co-MnO2 catalyst as described in the first aspect or the dual MOFs-derived composite carbon-based loaded Co-MnO2 catalyst obtained by the preparation method described in the second aspect in the catalytic reduction of nitrobenzene substances to amine substances.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] The present invention provides a dual MOFs-derived composite carbon-based supported Co-MnO2 catalyst, a preparation method and an application thereof. The catalyst has good catalytic activity, selectivity and stability, as well as excellent magnetic separation performance, and shows good application prospects in the field of nanocatalysis, especially in the field of selective catalytic reduction reaction, which is mainly manifested in the following aspects:
[0029] (1) The miniaturization of ZIF-67 to obtain small-sized nanoparticles helps to reduce the size of the derivative catalyst and improve its dispersibility in the reaction medium, thereby significantly enhancing its catalytic performance. The process of constructing small-sized ZIF-67 nanoparticles forms a dual MOFs core-shell composite structure, which increases the specific surface area of the catalyst, improves the micro-reaction environment of the composite carrier interface, and promotes the anchoring and solidification of the metal active sites, thereby giving the catalyst a better carrier effect.
[0030] (2) Synthesis of dual MOFs-derived composite carbon-based materials under high temperature calcination in an inert atmosphere, Co immobilized on ZIF-67 2+ and Mn 2+ The ions are in situ converted into magnetic Co-MnO2 complexes and anchored in the derived nitrogen-doped carbon layer, providing strong Lewis base sites and hydrogen absorption active sites, which help to enhance the electron transfer efficiency of the catalytic reaction. Moreover, the physical topology and interfacial chemical effects of the dual MOFs derivatives can produce a good synergistic effect with the bimetallic complex, forming a bimetallic catalytic active site between the Co nanoparticles and the MnO2 particles, constructing an enhanced synergistic effect and bimetallic electronic effect between the two, thereby greatly improving the catalytic performance of the catalyst.
[0031] (3) The dual-MOFs-derived composite carbon-based material serves as an in-situ encapsulation structure of the Co-MnO2 complex, which effectively inhibits the agglomeration and loss tendency of the metal catalytic active sites in the catalytic reaction, thereby enhancing the stability of the catalyst; at the same time, the Co-MnO2 complex has a strong magnetization intensity, which makes the catalyst exhibit excellent magnetic separation performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 is the TEM image of the Ce-BTC@ZIF-67 composite material prepared in Example 1.
[0033] Figure 2 This is the TEM image of the dual MOFs-derived composite carbon-based supported Co-MnO2 catalyst prepared in Example 1.
[0034] Figure 3 This is the element mapping distribution diagram of the dual MOFs derived composite carbon-based supported Co-MnO2 catalyst prepared in Example 1.
[0035] Figure 4 This is a magnetic separation diagram of the dual MOFs-derived composite carbon-based supported Co-MnO2 catalyst prepared in Example 1.
[0036] Figure 5 This is the TEM image of the ZIF-67 material prepared in Comparative Example 1. DETAILED DESCRIPTION
[0037] The present invention is further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention. After reading the present invention, modifications of various equivalent forms of the present invention by those skilled in the art all fall within the scope defined by the requirements of this application.
[0038] The present invention provides a dual MOFs-derived composite carbon-based Co-MnO2 catalyst, a preparation method and an application thereof. The catalyst first synthesizes Ce-BTC nanorods as a carrier, and after being activated by a hydrochloric acid solution, Co is immobilized by utilizing the electrostatic adsorption effect of the carbonyl groups on its surface. 2+ ions, and then triggered a continuous bridging reaction with 2-methylimidazole ligands to in situ form small-sized ZIF-67 nanoparticles on the Ce-BTC surface to obtain Ce-BTC@ZIF-67 core-shell composites; then, Mn was doped into the ZIF-67 precursor by ion exchange. 2+ ions, and finally calcined in an inert atmosphere to form a dual MOFs-derived composite carbon-based supported Co-MnO2 catalyst (CeO2-C@NC / Co-MnO2) with a one-dimensional hollow nano core-shell structure. The catalyst effectively constructs a Co-MnO2 binary metal active combination, improves the catalytic activity and stability of Co nanoparticles, and improves the micro-reaction environment of Co nanoparticles. The catalyst has good magnetic separation performance and exhibits high catalytic activity, selectivity and stability in the catalytic reaction of reducing nitrobenzene substances to amine substances.
[0039] The following is an explanation through specific embodiments.
[0040] Example 1
[0041] At room temperature, 2.17 g of cerium nitrate hexahydrate and 1.05 g of trimesic acid were dispersed in a mixed solution of 50 mL of deionized water and 50 mL of ethanol, and magnetic stirring was performed for 0.5 h. The temperature was then raised to 90 ° C. and refluxed and stirred for 2 h under constant temperature conditions. After cooling to room temperature, the white solid was collected by centrifugation, washed with ethanol, and dried at 45 ° C for 12 h to obtain Ce-BTC nanorods.
[0042] At room temperature, 0.2 g of the above Ce-BTC solid was ultrasonically dispersed in 20 mL of ethanol, and 20 mL of ethanol solution containing 0.58 g of cobalt nitrate hexahydrate and 1 mL of hydrochloric acid solution (0.2 mol / L) was added, and the mixture was magnetically stirred for 0.5 h. Then, 40 mL of ethanol solution containing 1.65 g of 2-methylimidazole was added, and the stirring and mixing was continued for 6 h. The purple solid was collected by centrifugation, washed with ethanol, and dried at 45 °C for 12 h to obtain the Ce-BTC@ZIF-67 core-shell composite material.
[0043] At room temperature, 0.2g of the above Ce-BTC@ZIF-67 solid was ultrasonically dispersed in 30mL of ethanol, and 30mL of ethanol solution containing 0.25g of hexahydrated manganese nitrate was added, and the mixture was stirred magnetically for 6h. The solid was collected by centrifugation, washed with ethanol, and dried at 45°C for 12h to obtain Ce-BTC@ZIF-67 / Mn composite material. Subsequently, the material was placed in a crucible ark, high-purity nitrogen was introduced, and the temperature was increased to 600°C at a heating rate of 2°C / min and kept constant for 2h to obtain a dual MOFs-derived composite carbon-based supported Co-MnO2 catalyst (CeO2-C@NC / Co-MnO2).
[0044] The structure of the Ce-BTC@ZIF-67 core-shell composite material prepared by the method of Example 1 is as follows: Figure 1 As shown in Figure 2, small-sized ZIF-67 nanoparticles are uniformly distributed on the surface of Ce-BTC nanorods, and the average particle size of these loaded ZIF-67 is 89±23.6nm. 2+ After ionization, the morphology and structure of the ZIF-67 precursor in the composite material did not change. After calcination in high-purity nitrogen, a dual MOFs-derived composite carbon-based supported Co-MnO2 catalyst (CeO2-C@NC / Co-MnO2) was obtained, and its structure is shown in Figure 2 The Ce-BTC@ZIF-67 / Mn composite material is transformed into a composite carbon-based structure. The Co immobilized on ZIF-67 2+ and Mn 2+ The ions are converted into Co-MnO2 complexes and anchored in the derived nitrogen-doped carbon layer structure for further encapsulation and solidification. Figure 3 Shows the spatial distribution characteristics of the main elements in the catalyst. Figure 4 It shows that the catalyst has good magnetic separation performance.
[0045] The dual MOFs-derived composite carbon-based supported Co-MnO2 catalyst (CeO2-C@NC / Co-MnO2) prepared by the method of Example 1 was used to evaluate the reaction performance of catalytic reduction of p-nitrophenol. The evaluation method is as follows: 30 mL of a mixed solution containing 25 mg / L p-nitrophenol and 63 mg / L sodium borohydride was measured in a reaction vessel, 3 mL of the prepared 1 g / L catalyst dispersion was added under stirring, and the catalytic reaction was started. A small amount of the reaction solution was taken for a certain reaction time and filtered through a polyethersulfone filter membrane, and the conversion rate of p-nitrophenol and the selectivity of p-aminophenol were analyzed by high performance liquid chromatography.
[0046] The results show that at 4 minutes of reaction, the conversion rate of p-nitrophenol catalytic reduction of the catalyst reaches 99.8%, and the selectivity of p-aminophenol is 100%. At this time, the first round of catalytic performance evaluation of the catalytic reaction is completed, and 5mL of a mixed solution containing 0.138g / L p-nitrophenol and 63mg / L sodium borohydride is continued to be added to the reaction solution for the second round of catalytic reaction. At 4 minutes of reaction, a small amount of reaction solution is taken to analyze the conversion rate of p-nitrophenol and the selectivity of p-aminophenol. After the 8th cycle test in this way, the conversion rate of p-nitrophenol catalytic reduction of the catalyst is 93.3%, and the selectivity of p-aminophenol is 100%. After the reaction is completed, the catalyst in the reaction solution is separated by a filter membrane, and the clear liquid obtained is subjected to ICP-OES analysis. The results show that the metal ion concentrations of Co and Mn are not detected, indicating that the active components of Co and Mn of the catalyst do not leach and lose during the catalytic reaction, and are still stable in the overall structure of the catalyst.
[0047] Comparative Example 1
[0048] At room temperature, first prepare 40 mL of ethanol solution containing 0.58 g of cobalt nitrate hexahydrate and 1 mL of hydrochloric acid solution (0.2 mol / L), add 40 mL of ethanol solution containing 1.65 g of 2-methylimidazole under magnetic stirring, continue stirring and mixing for 6 h, collect the purple solid by centrifugation, wash with ethanol, and dry at 45 °C for 12 h to obtain ZIF-67 material.
[0049] At room temperature, 0.2 g of the above ZIF-67 solid was ultrasonically dispersed in 30 mL of ethanol, and 30 mL of ethanol solution containing 0.25 g of manganese nitrate hexahydrate was added, and the mixture was stirred magnetically for 6 h. The solid was collected by centrifugation, washed with ethanol, and dried at 45 ° C for 12 h to obtain ZIF-67 / Mn material. Subsequently, the material was placed in a crucible ark, high-purity nitrogen was introduced, and the temperature was increased to 600 ° C at a heating rate of 2 ° C / min and kept at a constant temperature for 2 h to obtain ZIF-67 derived carbon-based supported Co-MnO2 catalyst (NC / Co-MnO2).
[0050] The difference between the method of comparative example 1 and the method of embodiment 1 is that there is no step of synthesizing Ce-BTC nanorods and adding them to the subsequent synthesis reaction, and the other experimental parameters and steps remain the same. The structure of the ZIF-67 material prepared by the method of comparative example 1 is as follows: Figure 5 As shown in the figure, it is a polyhedral structure with an average particle size of 330±45.5nm, which is much larger than the average particle size of ZIF-67 particles in Ce-BTC@ZIF-67 composite materials. 2+After ionization, the morphology and structure of the ZIF-67 precursor did not change. After calcination in high-purity nitrogen, the ZIF-67-derived carbon-based supported Co-MnO2 catalyst (NC / Co-MnO2) was obtained. 2+ and Mn 2+ ions are transformed into Co-MnO2 complexes anchored in ZIF-67-derived graphitized carbon-based structures.
[0051] The ZIF-67 derived carbon-based supported Co-MnO2 catalyst (NC / Co-MnO2) prepared by the method of Comparative Example 1 was used to evaluate the catalytic reduction reaction performance of p-nitrophenol. The evaluation method is as follows: 30 mL of a mixed solution containing 25 mg / L p-nitrophenol and 63 mg / L sodium borohydride was measured in a reaction vessel, 3 mL of the prepared 1 g / L catalyst dispersion was added under stirring, and the catalytic reaction was started. A small amount of the reaction solution was taken for a certain period of time for each reaction and filtered through a polyethersulfone filter membrane, and the conversion rate of p-nitrophenol and the selectivity of p-aminophenol were analyzed by high performance liquid chromatography.
[0052] The results showed that at 4 minutes of reaction, the conversion rate of NC / Co-MnO2 catalyst for the catalytic reduction of p-nitrophenol reached 82.5%, and the selectivity for p-aminophenol was 100%. At the same time, the pseudo-first-order reaction kinetic model was fitted, and the apparent reaction kinetic rate constant of NC / Co-MnO2 catalyst was calculated to be 0.638min -1 The apparent reaction kinetic rate constant of the dual MOFs-derived composite carbon-based supported Co-MnO2 catalyst (CeO2-C@NC / Co-MnO2) is 1.562min -1 The results show that the catalytic reduction efficiency of 4-nitrophenol by NC / Co-MnO2 catalyst is far inferior to that of CeO2-C@NC / Co-MnO2 catalyst; the unique dual MOFs composite structure design and the construction of small-sized ZIF-67 nanoparticles of CeO2-C@NC / Co-MnO2 catalyst make it show excellent catalytic performance.
[0053] Comparative Example 2
[0054] The Ce-BTC nanorods were synthesized by the method of Example 1. The material was placed in a crucible ark, high-purity nitrogen was introduced, and the temperature was increased to 600°C at a heating rate of 2°C / min and kept at a constant temperature for 2h to obtain CeO2-C nanotubes. The prepared CeO2-C nanotubes were evaluated for their catalytic reduction performance of p-nitrophenol, and the evaluation method was consistent with the method of Example 1. The results showed that after 4 minutes of reaction, the conversion rate of p-nitrophenol catalytic reduction by CeO2-C nanotubes reached 25.1%, and the selectivity for p-aminophenol was 100%. At the same time, a pseudo-first-order reaction kinetic model was fitted, and the apparent reaction kinetic rate constant of CeO2-C nanotubes was calculated to be 0.106min -1 The results show that the reaction efficiency of CeO2-C nanotubes in catalytic reduction of p-nitrophenol is far inferior to that of CeO2-C@NC / Co-MnO2 catalyst; the construction of dual MOFs composite carbon-based materials and Co-MnO2 composites endows the target catalyst with excellent catalytic performance.
[0055] Comparative Example 3
[0056] The Ce-BTC@ZIF-67 core-shell composite material was synthesized by the method of Example 1. The material was placed in a crucible ark, high-purity nitrogen was introduced, and the temperature was raised to 600°C at a heating rate of 2°C / min and kept constant for 2h to obtain a dual MOFs-derived composite carbon-based Co catalyst (CeO2-C@NC / Co). The prepared CeO2-C@NC / Co catalyst was evaluated for the catalytic reduction of p-nitrophenol, and the evaluation method was consistent with the method of Example 1. The results showed that at 4 minutes of reaction, the conversion rate of the CeO2-C@NC / Co catalyst for the catalytic reduction of p-nitrophenol reached 81.8%, and the selectivity for p-aminophenol was 100%. At the same time, the pseudo-first-order reaction kinetic model was fitted, and the apparent reaction kinetic rate constant of the CeO2-C@NC / Co catalyst was calculated to be 0.593min -1 The results show that the catalytic reduction efficiency of 4-nitrophenol by CeO2-C@NC / Co catalyst is far lower than that by CeO2-C@NC / Co-MnO2 catalyst; the construction of Co-MnO2 complex forms bimetallic catalytic active sites, constructs the enhanced synergistic effect and bimetallic electronic effect of the two, and greatly improves the catalytic performance of the target catalyst.
[0057] Example 2
[0058] At room temperature, 3.54 g of ammonium cerium nitrate and 2.18 g of trimesic acid were dispersed in a mixed solution of 45 mL of deionized water and 65 mL of ethanol, and magnetic stirring was performed for 0.5 h. The temperature was then raised to 80 ° C. and refluxed and stirred for 5 h under constant temperature conditions. After cooling to room temperature, the white solid was collected by centrifugation, washed with ethanol, and dried at 45 ° C for 12 h to obtain Ce-BTC nanorods.
[0059] At room temperature, 0.3 g of the above Ce-BTC solid was ultrasonically dispersed in 30 mL of ethanol, and 30 mL of ethanol solution containing 1.15 g of cobalt chloride and 1 mL of hydrochloric acid solution (0.2 mol / L) was added, and the mixture was magnetically stirred for 0.5 h. Then, 35 mL of ethanol solution containing 2.96 g of 2-methylimidazole was added, and the stirring and mixing was continued for 8 h. The purple solid was collected by centrifugation, washed with ethanol, and dried at 45 °C for 12 h to obtain the Ce-BTC@ZIF-67 composite material.
[0060] At room temperature, 0.3g of the above Ce-BTC@ZIF-67 solid was ultrasonically dispersed in 40mL of ethanol, and 40mL of ethanol solution containing 0.57g of manganese sulfate tetrahydrate was added, and magnetic stirring was performed for 6h. The solid was collected by centrifugation, washed with ethanol, and dried at 45°C for 12h to obtain Ce-BTC@ZIF-67 / Mn composite material. Subsequently, the material was placed in a crucible ark, high-purity argon was introduced, and the temperature was increased to 550°C at a heating rate of 2°C / min and kept at a constant temperature for 3h to obtain a dual MOFs-derived composite carbon-based supported Co-MnO2 catalyst (CeO2-C@NC / Co-MnO2).
[0061] The Ce-BTC@ZIF-67 composite material prepared by the method of Example 2 shows that small-sized ZIF-67 nanoparticles are evenly distributed on the surface of Ce-BTC nanorods. 2+ After ionization, the morphology and structure of the ZIF-67 precursor in the composite material did not change. After calcination in high-purity argon, a dual MOFs-derived composite carbon-based supported Co-MnO2 catalyst (CeO2-C@NC / Co-MnO2) was obtained. The Ce-BTC@ZIF-67 / Mn composite material was converted into a one-dimensional hollow composite carbon-based structure, and the Co immobilized on ZIF-67 2+ and Mn 2+ The ions are converted into Co-MnO2 complexes and anchored in the derived nitrogen-doped carbon layer structure for further encapsulation and solidification.
[0062] The dual MOFs-derived composite carbon-based supported Co-MnO2 catalyst (CeO2-C@NC / Co-MnO2) prepared by the method of Example 2 was used to test the reaction performance of catalytic reduction of o-nitrophenol and m-nitrophenol. The evaluation method is as follows: 30 mL of a mixed solution containing 25 mg / L of the above-mentioned nitrobenzene substances and 63 mg / L of sodium borohydride was measured in a reaction vessel, 3 mL of the prepared 1 g / L catalyst dispersion was added under stirring, and the catalytic reaction was started. After a certain period of time in each reaction, a small amount of the reaction solution was filtered through a polyethersulfone filter membrane, and the conversion rate of the above-mentioned nitrobenzene substances and the selectivity of their product amine substances were analyzed by high performance liquid chromatography. The results showed that at 4 minutes of reaction, the conversion rate of o-nitrophenol catalytic reduction of this catalyst reached 99.1%, and the selectivity of o-aminophenol was 100%. At 4 minutes of reaction, the conversion rate of m-nitrophenol catalytic reduction of this catalyst reached 99.3%, and the selectivity of m-aminophenol was 100% Example 3
[0063] At room temperature, 3.87 g of cerium sulfate tetrahydrate and 2.66 g of trimesic acid were dispersed in a mixed solution of 55 mL of deionized water and 60 mL of ethanol, and magnetic stirring was performed for 0.5 h. The temperature was then raised to 85 ° C. and refluxed and stirred for 4 h under constant temperature conditions. After cooling to room temperature, the white solid was collected by centrifugation, washed with ethanol, and dried at 45 ° C for 12 h to obtain Ce-BTC nanorods.
[0064] At room temperature, 0.25 g of the above Ce-BTC solid was ultrasonically dispersed in 30 mL of ethanol, and 30 mL of ethanol solution containing 0.92 g of cobalt nitrate hexahydrate and 1 mL of hydrochloric acid solution (0.2 mol / L) was added, and the mixture was magnetically stirred for 0.5 h. Then, 30 mL of ethanol solution containing 2.55 g of 2-methylimidazole was added, and the stirring and mixing was continued for 9 h. The purple solid was collected by centrifugation, washed with ethanol, and dried at 50 °C for 10 h to obtain the Ce-BTC@ZIF-67 composite material.
[0065] At room temperature, 0.25g of the above Ce-BTC@ZIF-67 solid was ultrasonically dispersed in 35mL of ethanol, and 40mL of ethanol solution containing 0.45g of manganese acetate was added, and the mixture was stirred magnetically for 8h. The solid was collected by centrifugation, washed with ethanol, and dried at 50°C for 10h to obtain Ce-BTC@ZIF-67 / Mn composite material. Subsequently, the material was placed in a crucible ark, high-purity helium was introduced, and the temperature was increased to 600°C at a heating rate of 3°C / min and kept at a constant temperature for 2h to obtain a dual MOFs-derived composite carbon-based supported Co-MnO2 catalyst (CeO2-C@NC / Co-MnO2).
[0066] The Ce-BTC@ZIF-67 composite material prepared by the method of Example 3 shows that small-sized ZIF-67 nanoparticles are evenly distributed on the surface of Ce-BTC nanorods. 2+ After ionization, the morphology and structure of the ZIF-67 precursor in the composite material did not change. After calcination in high-purity helium, a dual MOFs-derived composite carbon-based supported Co-MnO2 catalyst (CeO2-C@NC / Co-MnO2) was obtained. The Ce-BTC@ZIF-67 / Mn composite material was converted into a one-dimensional hollow composite carbon-based structure, and the ZIF-67-immobilized Co 2+ and Mn 2+ The ions are converted into Co-MnO2 complexes and anchored in the derived nitrogen-doped carbon layer structure for further encapsulation and solidification.
[0067] The dual MOFs-derived composite carbon-based supported Co-MnO2 catalyst (CeO2-C@NC / Co-MnO2) prepared by the method of Example 3 was used to test the reaction performance of catalytic reduction of p-nitrophenol with different substituted groups (including 2-fluoro-4-nitrophenol, 2-chloro-4-nitrophenol, 2-bromo-4-nitrophenol, 2-methyl-4-nitrophenol and 2-methoxy-4-nitrophenol). The evaluation method is as follows: 30 mL of a mixed solution containing 0.18 mmol / L of the above-mentioned nitrobenzene substances and 63 mg / L of sodium borohydride was measured in a reaction container, 3 mL of the prepared 1 g / L catalyst dispersion was added under stirring, and the catalytic reaction was started. A small amount of the reaction solution was taken for a certain reaction time and filtered through a polyethersulfone filter membrane, and the conversion rate of the above-mentioned nitrobenzene substances and the selectivity of the product amine substances were analyzed by high performance liquid chromatography.
[0068] The results show that at 4 minutes of reaction, the conversion rate of 2-fluoro-4-nitrophenol catalytic reduction by the catalyst reaches 99.5%, and the selectivity of 2-fluoro-4-aminophenol is 100%. At 4 minutes of reaction, the conversion rate of 2-chloro-4-nitrophenol catalytic reduction by the catalyst reaches 99.7%, and the selectivity of 2-chloro-4-aminophenol is 100%. At 4 minutes of reaction, the conversion rate of 2-bromo-4-nitrophenol catalytic reduction by the catalyst reaches 99.4%, and the selectivity of 2-bromo-4-aminophenol is 100%. At 4 minutes of reaction, the conversion rate of 2-methyl-4-nitrophenol catalytic reduction by the catalyst reaches 99.4%, and the selectivity of 2-methyl-4-aminophenol is 100%. At 4 minutes of reaction, the conversion rate of 2-methoxy-4-nitrophenol catalytic reduction by the catalyst reaches 99.5%, and the selectivity of 2-methoxy-4-aminophenol is 100%.
[0069] Example 4
[0070] At room temperature, 4.06 g of cerium chloride heptahydrate and 2.83 g of trimesic acid were dispersed in a mixed solution of 50 mL of deionized water and 55 mL of ethanol, and magnetically stirred for 0.5 h. The mixture was then heated to 86 ° C and refluxed with stirring for 4 h under constant temperature conditions. After cooling to room temperature, the white solid was collected by centrifugation, washed with ethanol, and dried at 50 ° C for 10 h to obtain Ce-BTC nanorods.
[0071] At room temperature, 0.28 g of the above Ce-BTC solid was ultrasonically dispersed in 30 mL of ethanol, and 30 mL of ethanol solution containing 1.05 g of cobalt sulfate heptahydrate and 1 mL of hydrochloric acid solution (0.2 mol / L) was added, and the mixture was magnetically stirred for 0.5 h. Then, 25 mL of ethanol solution containing 2.76 g of 2-methylimidazole was added, and the stirring and mixing was continued for 7 h. The purple solid was collected by centrifugation, washed with ethanol, and dried at 45 °C for 12 h to obtain the Ce-BTC@ZIF-67 composite material.
[0072] At room temperature, 0.28g of the above Ce-BTC@ZIF-67 solid was ultrasonically dispersed in 40mL of ethanol, and 35mL of ethanol solution containing 0.46g of hexahydrated manganese nitrate was added, and the mixture was stirred magnetically for 7h. The solid was collected by centrifugation, washed with ethanol, and dried at 50°C for 12h to obtain Ce-BTC@ZIF-67 / Mn composite material. Subsequently, the material was placed in a crucible ark, high-purity argon was introduced, and the temperature was increased to 580°C at a heating rate of 2°C / min and kept at a constant temperature for 2.5h to obtain a dual MOFs-derived composite carbon-based supported Co-MnO2 catalyst (CeO2-C@NC / Co-MnO2).
[0073] The Ce-BTC@ZIF-67 composite material prepared by the method of Example 4 shows that small-sized ZIF-67 nanoparticles are evenly distributed on the surface of Ce-BTC nanorods. 2+ After ionization, the morphology and structure of the ZIF-67 precursor in the composite material did not change. After calcination in high-purity argon, a dual MOFs-derived composite carbon-based supported Co-MnO2 catalyst (CeO2-C@NC / Co-MnO2) was obtained. The Ce-BTC@ZIF-67 / Mn composite material was converted into a one-dimensional hollow composite carbon-based structure, and the Co immobilized on ZIF-67 2+ and Mn 2+ The ions are converted into Co-MnO2 complexes and anchored in the derived nitrogen-doped carbon layer structure for further encapsulation and solidification.
[0074] The dual MOFs-derived composite carbon-based supported Co-MnO2 catalyst (CeO2-C@NC / Co-MnO2) prepared by the method of Example 4 was used to test the reaction performance of catalytic reduction of nitroaniline (including o-nitroaniline, m-nitroaniline and p-nitroaniline). The evaluation method is as follows: 30 mL of a mixed solution containing 0.18 mmol / L of the above-mentioned nitrobenzene substances and 63 mg / L of sodium borohydride was measured in a reaction container, 3 mL of the prepared 1 g / L catalyst dispersion was added under stirring, and the catalytic reaction was started. A small amount of the reaction solution was taken for a certain reaction time and filtered through a polyethersulfone filter membrane, and the conversion rate of the above-mentioned nitrobenzene substances and the selectivity of the product amine substances were analyzed by high performance liquid chromatography.
[0075] The results show that at 7 minutes of reaction, the conversion rate of o-nitroaniline catalytic reduction of the catalyst reached 98.7%, and the selectivity of o-phenylenediamine was 100%. At 7 minutes of reaction, the conversion rate of m-nitroaniline catalytic reduction of the catalyst reached 86.9%, and the selectivity of m-phenylenediamine was 100%. At 5 minutes of reaction, the conversion rate of p-nitroaniline catalytic reduction of the catalyst reached 99.1%, and the selectivity of p-phenylenediamine was 100%.
[0076] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable ordinary technicians in the field to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made based on the essence of the content of the present invention should be included in the protection scope of the present invention.
Claims
1. A dual MOFs derived composite carbon-based supported Co-MnO2 catalyst, characterized in that: include: Dual MOFs-derived composite carbon-based material and CeO2: The dual MOFs-derived composite carbon-based material and CeO2 are prepared by first in-situ growing ZIF-67 nanoparticles on the surface of Ce-BTC nanorods to obtain Ce-BTC@ZIF-67 core-shell composite materials, and then calcining in an inert atmosphere; and, Co-MnO2 composite: The Co-MnO2 composite is the Ce-BTC@ZIF-67 core-shell composite material doped with Mn by ion exchange method. 2+ ions, and then the Co immobilized on ZIF-67 2+ and Mn 2+ The ions are formed by in situ transformation; The Ce-BTC nanorods are obtained by heating and refluxing reaction of cerium salt and trimesic acid.
2. The dual MOFs derived composite carbon-based supported Co-MnO2 catalyst according to claim 1, characterized in that: In the Ce-BTC@ZIF-67 core-shell composite material, Ce-BTC nanorods are calcined in an inert atmosphere to form CeO2-C nanotubes, wherein the CeO2-C nanotubes contain carbon material and CeO2, wherein the carbon material is reacted to form a dual MOFs-derived composite carbon-based material; and the ZIF-67 nanoparticles and Ce-BTC nanorods are composited and reacted to form a dual MOFs-derived composite carbon-based material. In the catalyst, the mass percentage of CeO2 is 10-30% of the catalyst, the mass percentage of the dual MOFs derived composite carbon-based material is 30-70% of the catalyst, and the mass percentage of the Co-MnO2 complex is 10-35% of the catalyst.
3. The dual MOFs derived composite carbon-based supported Co-MnO2 catalyst according to claim 1, characterized in that: The Co-MnO2 composite consists of Co nanoparticles and MnO2 nanoparticles, the mass percentage of the Co nanoparticles is 8-20% of the catalyst, and the mass percentage of the Mn component is 2-10% of the catalyst.
4. The method for preparing the dual MOFs-derived composite carbon-based supported Co-MnO2 catalyst according to any one of claims 1 to 3, characterized in that: The steps include: (1) Ce-BTC nanorods were obtained by heating and refluxing cerium salt and trimesic acid. After Ce-BTC nanorods were activated by hydrochloric acid solution, Co was immobilized by the electrostatic adsorption effect of the carbonyl groups on their surface. 2+ ions, and then triggered a continuous bridging reaction with 2-methylimidazole ligands to in situ form ZIF-67 nanoparticles on the Ce-BTC surface to obtain Ce-BTC@ZIF-67 core-shell composites; (2) The ZIF-67 particles in the Ce-BTC@ZIF-67 core-shell composite were subjected to Mn 2+ Ion doping, followed by calcination in an inert atmosphere, caused the Ce-BTC@ZIF-67 / Mn material to undergo a pyrolysis reaction to form a dual MOFs-derived composite carbon-based material and CeO2, while the Co immobilized on ZIF-67 2+ and Mn 2+ ions are in situ converted into a Co-MnO2 complex to obtain the dual MOFs-derived composite carbon-based supported Co-MnO2 catalyst CeO2-C@NC / Co-MnO2.
5. The method for preparing the dual MOFs-derived composite carbon-based supported Co-MnO2 catalyst according to claim 4, characterized in that: In step (1), the preparation process of the Ce-BTC@ZIF-67 core-shell composite material is as follows: a) dispersing and dissolving cerium salt and trimesic acid in a mixed solution of deionized water and ethanol, stirring and mixing for 0.5 to 1 hour, then heating to 60 to 95° C., heating under reflux for 2 to 10 hours, cooling to room temperature, centrifuging, washing, and drying to obtain Ce-BTC nanorods; b) Ce-BTC nanorods are dispersed in ethanol, an ethanol solution containing a cobalt salt and a hydrochloric acid solution is added, and the mixture is stirred for 0.5 to 1 h, and then a 2-methylimidazole ethanol solution is added, and the mixture is stirred and reacted at room temperature for 4 to 12 h, and the mixture is centrifuged, washed, and dried to obtain a Ce-BTC@ZIF-67 composite material.
6. The method for preparing the dual MOFs-derived composite carbon-based supported Co-MnO2 catalyst according to claim 5, characterized in that: In step a), the mass ratio of the cerium salt to trimesic acid is 1:0.2-1; the volume ratio of the deionized water to ethanol is 1:0.5-1.5; and the cerium salt is any one of cerium nitrate, ammonium cerium nitrate, cerium sulfate, cerium chloride and cerium acetate.
7. The method for preparing the dual MOFs-derived composite carbon-based supported Co-MnO2 catalyst according to claim 5, characterized in that: In step b), the mass ratio of the Ce-BTC nanorods, the cobalt salt, the 2-methylimidazole and the total amount of ethanol used is 1:2-10:4-20:150-360; the volume ratio of the hydrochloric acid solution to the total amount of ethanol used is 1:50-100; the molar concentration of hydrogen chloride in the hydrochloric acid solution is 0.1-0.5 mol / L; and the cobalt salt is any one of cobalt nitrate, cobalt chloride, cobalt sulfate and cobalt acetate.
8. The method for preparing a dual MOFs-derived composite carbon-based supported Co-MnO2 catalyst according to claim 4, characterized in that: In step (2), the preparation process of the dual MOF-derived composite carbon-based supported Co-MnO2 catalyst comprises the following steps: The Ce-BTC@ZIF-67 composite material is dispersed in an ethanol solution, an ethanol solution containing manganese salt is added, the mixture is stirred and mixed at room temperature for 4 to 10 hours, centrifuged, washed, and dried to obtain a Ce-BTC@ZIF-67 / Mn composite material; the composite material is then placed in an inert atmosphere for high-temperature calcination to obtain a dual-MOFs derived composite carbon-based supported Co-MnO2 catalyst CeO2-C@NC / Co-MnO2.
9. The method for preparing the dual MOFs-derived composite carbon-based supported Co-MnO2 catalyst according to claim 8, characterized in that: The mass ratio of the total amount of Ce-BTC@ZIF-67 composite material, manganese salt and ethanol used is 1:0.5-5:150-360; the inert atmosphere is selected from any one of nitrogen, argon and helium; the manganese salt is any one of manganese nitrate, manganese chloride, manganese sulfate and manganese acetate; the inert atmosphere calcination treatment conditions are: 1-5°C / min heating rate, heating to 500-1000°C and maintaining a constant temperature for 1-5h.
10. Use of the dual-MOFs-derived composite carbon-based supported Co-MnO2 catalyst as described in any one of claims 1 to 3 or the dual-MOFs-derived composite carbon-based supported Co-MnO2 catalyst obtained by the preparation method as described in any one of claims 4 to 9 in catalytic reduction of nitrobenzene substances to amine substances.